Determination of HIV/AIDS Risk Behavioural Factors Among University of Dodoma Students in Tanzania - Abbas, Ismail; Akarro, R. R. J. (Tanzania Journal for Population studies and Development, 2011)
This study was conducted among university students at the University of Dodoma, and sought to determine whether knowledge on HIV/AIDS, attitudes and beliefs can predict practices that causes HIV infections. A pre-designed questionnaire was administered in this cross-sectional study in a sample of 547 (539 students plus 8 lecturers). The data on responses of students to HIV/AIDS related knowledge, attitudes and beliefs were analyzed preliminarily using frequencies and cross tabulations. Ordinal Logistic Regression (OLR) was used in analyzing the relationship between the dependent and independent variables. The OLR for sex under the influence of alcohol (p<0.001) had significant contribution from gender, knowledge on transmission through sexual contact, beliefs about HIV/AIDS and attitudes toward VCT testing. The OLR for sex without condom (p<0.001) had significant contributions from gender and attitudes toward condom use. Knowledge on transmission through sexual contact, beliefs about HIV/AIDS, attitudes toward VCT testing, and condom use appeared to be common predictors of HIV/AIDS risk behavioural factors among students.